A history of the teaching of English language in the Philippine public schools - Manhit, Basilisa J. 1918- (Quezon City, Philippines College of Education, University of the Philippines Diliman, 1950)
It is the prime object of this study to answer the following questions: (1) what has been the educational policy of the government on the teaching of the English language in the Philippine public schools; amd (2) what have been the changes in the curriculum, methods and requirements in the teaching of English in the Philippine public schools.
Mimeographed.
Vita.
Thesis (M.A.)--University of the Philippines, Diliman.
Keywords: English language -- Study and teaching -- Philippine students